Preparation method of copper-magnetic co-fired inductor and copper-magnetic co-fired inductor
By performing surface treatment on copper powder and a multi-stage sintering process, a copper co-fired inductor with an Al2O3/HfO2/SiO2 three-layer composite passivation-diffusion barrier layer is formed, which solves the problems of interfacial bonding and stability in existing copper co-fired inductors and achieves high conductivity, high magnetic properties and excellent environmental stability.
Patent Information
- Application Number
- CN202511384511.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-26
- Publication Date
- 2025-11-11
AI Technical Summary
Existing technologies cannot provide copper co-fired inductors that combine high conductivity, high magnetic properties, strong interfacial bonding, and excellent environmental stability, resulting in challenges in terms of microstructure integrity, interfacial bonding strength, and long-term reliability.
A three-layer composite passivation-diffusion barrier layer of Al2O3/HfO2/SiO2 is formed by atomic layer deposition of surface-pretreated copper powder in a fluidized bed reactor. The copper electrode slurry is mixed with an organic carrier to form a comb-shaped electrode structure by screen printing. The slurry is alternately stacked with modified Ni-Zn ferrite green sheets, and then subjected to multi-stage gradient sintering and isothermal diffusion annealing to form a copper co-fired inductor.
Thermodynamic stability, kinetic controllability, and interfacial chemical inertness of the copper electrode and the magnetic substrate were achieved, forming a three-dimensional interlocked composite system, which improved the overall performance and reliability of the device.
Smart Images

Figure CN120933056A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of electronic component manufacturing technology, and in particular to a method for preparing a copper co-fired inductor and the copper co-fired inductor itself. Background Technology
[0002] In the context of the rapid development of modern electronics industry, power inductors, as core passive components in energy conversion and filtering systems, directly determine the efficiency, stability, and miniaturization level of power modules. Especially in high-power-density applications such as 5G communication base stations, electric drive systems for new energy vehicles, server power supplies, and high-frequency DC-DC converters, inductors are required to possess comprehensive performance characteristics including low DC resistance, high saturation flux density, excellent high-frequency characteristics, and high mechanical stability.
[0003] Traditional inductor manufacturing processes often use silver or copper paste as conductive internal electrodes, which are integrated with ferrite or metal magnetic powder materials through stacking co-firing or wire-wound packaging processes. While silver electrodes have good sintering compatibility and conductivity, their high cost and low conductivity have revealed dual bottlenecks in terms of economy and physical performance for large-scale mass production and high-efficiency applications. Although copper electrodes have significant advantages in conductivity and cost control, their inherent characteristics, such as easy oxidation during high-temperature sintering, mismatch with the thermal expansion coefficient of magnetic materials, and violent interfacial reactions, have made it difficult to achieve co-dense sintering with the magnetic substrate. This has resulted in insurmountable technical obstacles in terms of device microstructure integrity, interfacial bonding strength, and long-term reliability. Summary of the Invention
[0004] The purpose of this invention is to provide a method for preparing a copper magnetic co-fired inductor and the copper magnetic co-fired inductor itself, so as to solve the technical problem that the prior art cannot provide a novel co-fired system that has high conductivity, high magnetic properties, strong interfacial bonding force and excellent environmental stability.
[0005] One aspect of the present invention provides a method for preparing a copper co-fired inductor, comprising: Spherical electrolytic copper powder with an average particle size of 0.8 μm to 2.5 μm was surface pretreated, and the pretreated copper powder was placed in a fluidized bed reactor for atomic layer deposition under a nitrogen atmosphere. Trimethylaluminum vapor and deionized water vapor are introduced, and deposition is carried out at 120°C for 15 to 40 cycles to form an initial passivation layer of aluminum oxide with a thickness of 3 nm to 8 nm. By switching the precursor to tetrahafnium and ozone, a hafnium oxide intermediate layer with a thickness of 5 nm to 12 nm is formed by deposition at 150 °C for 20 to 50 cycles. Then, by switching the precursor to trisilane and oxygen, a silicon dioxide outer layer with a thickness of 8 nm to 15 nm is formed by deposition at 180 °C for 25 to 60 cycles. This yields modified copper powder with a three-layer composite passivation-diffusion barrier layer of Al2O3 / HfO2 / SiO2 on the surface. The modified copper powder was mixed with an organic carrier at a mass ratio of 75:25 and then milled by three rollers for 4 hours to obtain a copper electrode slurry with a viscosity of 8000 cP to 12000 cP and a solid content of 75 wt%. The copper electrode paste is screen-printed onto a green ceramic tape with a thickness of 50μm to 150μm to form a comb-shaped electrode structure with a width of 0.1mm to 0.5mm and a spacing of 0.05mm to 0.2mm. After printing, it is dried at 80°C for 10 minutes to form a copper electrode green layer. Modified Ni-Zn ferrite green sheets are provided, which are mixed with polyvinyl butyral at a mass ratio of 95:5 and then pressed into magnetic green sheets with a thickness of 100μm to 300μm. The copper electrode green sheet and the magnetic green sheet are alternately stacked to form a stacked structure of 3 to 15 copper electrodes. Each magnetic green sheet is located between two adjacent copper electrode layers. The stacking pressure is 50 MPa to 100 MPa, and the pressure is held for 30 seconds to obtain a stacked green body. The stacked green body is placed in an atmosphere-controlled sintering furnace and multi-stage gradient sintering is performed, namely the first stage of debinding, the second stage of pre-sintering, the third stage of co-firing densification, and the fourth stage of cooling. After sintering, the end face of the inductor blank is ground and cleaned, silver paste is applied to form silver terminal electrodes, and an epoxy resin encapsulation layer is applied to the surface of the device.
[0006] In some embodiments, after the co-firing densification stage and before the cooling stage, an isothermal diffusion annealing step is added: under a nitrogen atmosphere at 1180°C, an isostatic pressure of 0.1 MPa to 0.5 MPa is applied for 30 to 90 minutes to induce the SiO2 component to diffuse to the interface to form a silicate transition layer with a thickness of 20 nm to 50 nm, thereby enhancing the interfacial bonding strength between the copper electrode and the magnetic substrate to greater than 45 MPa.
[0007] In some embodiments, the copper electrode slurry contains nano-magnesium oxide particles with a particle size of 50 nm to 200 nm, and the amount added is 0.5% to 2.0% of the mass of the copper powder.
[0008] In some embodiments, the laminated green body undergoes isostatic pressing pretreatment before co-firing: it is held at 200MPa to 300MPa for 5 minutes with 25°C silicone oil as the medium, so that the green body density is increased to more than 65% of the theoretical density and the difference in linear shrinkage between the copper electrode and the magnetic matrix is less than 0.7%.
[0009] In some embodiments, the sintering furnace employs a zoned temperature control structure during the co-firing densification stage. The furnace chamber has six independent temperature zones, each 100mm in length, with a temperature control accuracy of ±1℃ and an axial temperature gradient of less than 5℃. An oxygen partial pressure sensor is also configured to control the oxygen content of the atmosphere to be within 10⁻¹. 5 The range is from 10⁻¹² atm to 10⁻¹² atm.
[0010] In some embodiments, the outer silicon dioxide layer is doped with 1% to 5% phosphorus during deposition, and triphosphine is introduced as a co-precursor to form a phosphosilicate glass structure; the alumina layer is doped with 0.1 at% to 0.5 at% fluorine during deposition, and boron trifluoride diethyl ether complex is introduced to reduce the dielectric constant to 7.5.
[0011] In some embodiments, before printing, the comb-shaped electrode structure is first formed by laser drilling on a green ceramic tape to form a through-hole structure with a hole diameter of 0.1 mm to 0.3 mm and a tolerance of ±5 μm. After the inner wall of the hole is treated with argon plasma, 100 nm nano silver sol is sprayed to form a conductive seed layer, and then copper paste is printed to fill it.
[0012] In some embodiments, after the cooling stage switches to an argon atmosphere at 600°C, a longitudinal magnetic field of 0.05T to 0.2T is simultaneously applied to guide copper grains to form along the direction of the magnetic field. <111> Texture; the magnetic green sheet is subjected to argon plasma activation treatment for 30 seconds before stacking, with a power density of 5W / cm².
[0013] In some embodiments, the epoxy resin encapsulation layer is doped with 5% by mass of nano-aluminum nitride particles with a particle size of 30nm to 100nm; the magnetic core is subjected to magnetic field heat treatment after sintering to make the magnetic core grains preferentially oriented along the magnetic field direction.
[0014] Another aspect of the present invention provides a copper co-fired inductor, which is prepared by the aforementioned method and includes a multilayer magnetic core, copper electrodes embedded inside the magnetic core, silver end electrodes located at both ends of the device, and an epoxy resin encapsulation layer covering the surface of the device. The multilayer magnetic core is formed by dense sintering of multiple modified Ni-Zn ferrite sheets; the copper electrode is formed by sintering copper particles coated with a three-layer composite passivation-diffusion barrier layer of Al2O3 / HfO2 / SiO2; the contact resistance between the silver end electrode and the copper electrode is less than 0.5mΩ; the thermal expansion coefficient of the epoxy resin encapsulation layer matches the multilayer magnetic core and the copper electrode within ±5ppm / ℃.
[0015] Compared with the prior art, the present invention has the following beneficial effects: The present invention modifies the interface of copper conductor materials at the microscale. Through precise control of magnetic matrix components, precision molding of layered structures, and sintering system with multi-stage atmosphere and temperature synergistic control, the present invention ultimately achieves a three-dimensional interlocked composite system in which the copper phase and the magnetic phase are thermodynamically stable, kinetically controllable, chemically inert at the interface, and structurally dense and synergistic in a high-temperature co-firing environment. Attached Figure Description
[0016] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0017] Figure 1 This is a flowchart of the preparation method of the copper co-fired inductor of the present invention; Figure 2 This is a schematic diagram of the copper co-fired inductor product of the present invention. Detailed Implementation
[0018] The following will be based on embodiments of the present invention. Figures 1-2 The technical solutions in the embodiments of the present invention will be clearly and completely described together. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments.
[0019] Explanation of terms in this invention: <111> Texture: It is a specific direction in copper materials where the performance is better. It is a crystal orientation index that describes the direction of atomic arrangement in the crystal. It specifically corresponds to a direction in which atoms are most tightly packed in copper (face-centered cubic structure).
[0020] Example 1 The following will elaborate on the detailed technical implementation from seven dimensions: raw material pretreatment, functional layer construction, slurry preparation, green body forming, sintering process, post-treatment packaging and performance verification.
[0021] First, spherical electrolytic copper powder with an average particle size of 0.8 μm to 2.5 μm underwent surface pretreatment. The copper powder was immersed in a 5 wt% dilute hydrochloric acid solution for 30 seconds to dissolve the naturally formed copper oxide and cuprous oxide films on the surface. It was then transferred to deionized water and treated in an ultrasonic cleaning tank at a frequency of 40 kHz and a power density of 0.5 W / cm² for 5 minutes to thoroughly remove residual acid and loose particles. The cleaned copper powder was then placed in a 60°C vacuum drying oven and dried for 2 hours at an absolute pressure below 10 Pa to obtain a clean, oxide-free active copper powder substrate. This pretreatment step ensures that subsequent atomic layer deposition processes can directly nucleate on the surface of the metallic copper, avoiding the deterioration of interfacial adhesion caused by oxide interlayers.
[0022] Furthermore, the pretreated copper powder was loaded into a fluidized bed atomic layer deposition reactor. The reaction chamber was pre-evacuated to below 1 Pa and purged three times with high-purity nitrogen to ensure an oxygen content below 1 ppm. The deposition process was carried out continuously in three stages: in the first stage, trimethylaluminum (TMA) vapor was introduced with a pulse duration of 0.1 seconds, followed by deionized water vapor with a pulse duration of 0.2 seconds. The purging time was 30 seconds for each stage. The deposition temperature was set at 120°C, and the number of cycles was 15 to 40. Finally, a dense alumina (Al2O3) initial passivation layer with a thickness of 3 nm to 8 nm was formed on the surface of the copper powder. This layer was firmly bonded to the copper substrate through Cu-O-Al chemical bonds, with measured bond energies of 3.2 eV to 3.5 eV. X-ray photoelectron spectroscopy (XPS) depth profiling confirmed the absence of interfacial desorption.
[0023] The second stage involves switching the precursors to tetratetra(dimethylamino)hafnium (TDMAHf) and ozone (O3). The TDMAHf pulse duration is 0.15 seconds, the O3 pulse duration is 0.3 seconds, the purge time is 30 seconds, the deposition temperature is increased to 150°C, and the cycle is repeated 20 to 50 times to form a hafnium oxide (HfO2) intermediate layer with a thickness of 5 nm to 12 nm. The ionic conductivity of this layer at a high temperature of 1200°C is less than 10⁻⁻⁻⁶ by impedance spectroscopy. 8 The S / cm concentration significantly hinders the diffusion of magnetic cations such as Fe²⁺, Ni²⁺, and Zn²⁺. In the third stage, the precursor is switched to tris(dimethylamino)silane (3DMAS) and oxygen (O₂). The 3DMAS pulse duration is 0.2 seconds, the O₂ pulse duration is 0.4 seconds, the purge time is 30 seconds, the deposition temperature is increased to 180℃, and the cycle is repeated 25 to 60 times to deposit a silicon dioxide (SiO₂) outer layer with a thickness of 8 nm to 15 nm.
[0024] The coefficient of thermal expansion of this layer is 0.5 × 10⁻ 6 / ℃, between copper (17×10⁻ 6 / ℃) and ferrite (10×10⁻ 6It acts as a stress buffer between ℃ and 6°C; its high-temperature viscosity is greater than 10. 8 Pa·s effectively inhibits the outward diffusion of copper atoms. The final Al2O3 / HfO2 / SiO2 three-layer composite passivation-diffusion barrier layer has a total thickness of 16nm to 35nm. Cross-sectional observation by transmission electron microscopy (TEM) shows that the interfaces of each layer are clear, without interdiffusion or pores, and the coverage reaches 100%.
[0025] In a preferred embodiment of the present invention, tris(dimethylamino)phosphine (TDMAP) is simultaneously introduced as a phosphorus-doped precursor during the SiO2 outer layer deposition process. The molar flow ratio of TDMAP to 3DMAS is controlled at 1:20 to 1:5, and the deposition temperature is maintained at 180°C, ultimately forming a phosphosilicate glass (PSG) structure with a phosphorus atom percentage of 1% to 5%. The viscosity of this structure decreases to 10 at 1200°C. 7 The increased flowability (Pa·s) effectively fills the interfacial micropores generated during copper particle sintering, improving density. Simultaneously, phosphorus doping increases the ion migration activation energy of the SiO2 layer by 0.3 eV, further suppressing the electromigration failure of copper ions under an electric field. During the Al2O3 layer deposition stage, boron trifluoride diethyl ether complex (BF3·OEt2) is simultaneously introduced at a molar ratio of 1:100 to 1:200 with TMA, forming a fluorinated alumina layer with a fluorine doping concentration of 0.1 at% to 0.5 at%. This reduces the dielectric constant from 9.8 to 7.5 and lowers high-frequency polarization loss by 18%.
[0026] Further, the modified copper powder was mixed with an organic carrier at a mass ratio of 75:25. The organic carrier consisted of ethyl cellulose (100 mPa·s viscosity grade), dibutyl phthalate (DBP), and terpineol at a mass ratio of 12:8:80. The mixing process was carried out in a planetary mixer at a speed of 300 rpm for 30 minutes. The mixture was then transferred to a three-roll mill and circulated for 4 hours at roller spacings of 50 μm, 30 μm, and 15 μm, respectively, to obtain a copper electrode slurry with a viscosity of 8000 cP to 12000 cP (25°C, Brookfield DV-II+ viscometer, rotor SC4-18) and a solid content of 75 wt%. Nano-sized magnesium oxide (MgO) particles with an average particle size of 50 nm to 200 nm were added to the slurry at an addition rate of 0.5% to 2.0% of the copper powder mass. The nanoparticles were ultrasonically modified with a 1wt% stearic acid-ethanol solution for 30 minutes, dried, and then blended with copper powder to ensure uniform dispersion in the organic carrier without agglomerates. During sintering, the nano-MgO was distributed at the copper grain boundaries. With a melting point as high as 2852℃, it remained solid at 1200℃, inhibiting abnormal copper grain growth through a pinning effect, thus controlling the average grain size of the final copper electrode within the range of 10μm ± 2μm.
[0027] In a preferred embodiment of the present invention, the copper electrode paste undergoes vacuum degassing before printing. The paste is placed in a sealed container and stirred at 200 rpm for 30 minutes under a vacuum of -0.09 MPa, with the ambient temperature controlled at 25 ± 1°C. This process eliminates micron-sized air bubbles within the paste, ensuring sharp edges, no burrs, and no broken lines in the subsequent screen-printed graphics. After degassing, the paste is allowed to stand for 24 hours to stabilize its rheological properties.
[0028] Furthermore, copper electrode paste was coated onto an alumina-based green ceramic tape with a thickness of 50μm to 150μm using screen printing. The printing screen was a 325-mesh stainless steel screen, the emulsion thickness was 15μm, the squeegee pressure was 0.3MPa, and the printing speed was 50mm / s. The printed pattern was a comb-shaped electrode structure with a line width of 0.1mm to 0.5mm and a line spacing of 0.05mm to 0.2mm. The printed thickness, measured by a laser thickness gauge, was 25μm to 40μm. After printing, the green body was dried in an 80℃ hot air circulating oven for 10 minutes, resulting in a solvent evaporation rate of over 99%, forming a crack-free and edge-free copper electrode green body.
[0029] Before printing, the green ceramic tape is pre-drilled with laser to a diameter of 0.1 mm to 0.3 mm and a hole position accuracy of ±5 μm. After the inner wall of the hole is treated with argon plasma for 30 seconds (power density 5 W / cm²), a layer of nano silver sol (particle size 20 nm, solid content 5 wt%) is sprayed on and pre-baked at 150°C for 5 minutes to form a conductive seed layer with a thickness of about 100 nm. Then, copper paste is printed to fill the hole, ensuring that the inner wall of the through hole forms a continuous low-resistance interface with the copper electrode.
[0030] In a preferred embodiment of the present invention, the magnetic material is a modified Ni-Zn ferrite with a chemical composition of (Ni0.4Zn0.6)Fe2O4. The specific molar ratio is Fe2O3 49.5 mol%, NiO 19.8 mol%, ZnO 29.7 mol%, and is doped with Bi2O3 0.3 mol% and V2O5 0.2 mol% as sintering aids. The raw material is high-purity oxide powder (purity ≥99.9%). Zirconia balls are used as the grinding medium in a zirconia ball mill jar at a ball-to-material ratio of 3:1, a rotation speed of 300 rpm, and wet milling for 4 hours using anhydrous ethanol as the medium. The final powder particle size distribution is D90 < 3.5 μm and D10 > 0.8 μm. The slurry is spray-dried and granulated, resulting in a particle sphericity > 0.9 and good flowability. Granulated powder and polyvinyl butyral (PVB) binder are mixed at a mass ratio of 95:5 and kneaded in a double planetary mixer for 30 minutes. Then, they are pressed into magnetic green sheets with a thickness of 100 μm to 300 μm in an isostatic press at a pressing pressure of 150 MPa and a holding time of 60 seconds. The green sheet density is 58% to 62% of the theoretical density.
[0031] Furthermore, the magnetic green blanks undergo surface plasma activation treatment before stacking. They are placed in a parallel-plate plasma reaction chamber, and pure argon gas is introduced at a pressure of 50 Pa and a radio frequency power of 100 W for 30 seconds. This increases the hydroxyl density on the green blank surface from the original 1 × 10¹³ hydroxyl groups / cm² to 5 × 10¹³ hydroxyl groups / cm². 4 With a density of over 1 / cm², it significantly enhances the interfacial adhesion between the substrate and the copper electrode green layer, and reduces interlayer slippage during the lamination process.
[0032] In a preferred embodiment of the present invention, copper electrode green sheets and magnetic green sheets are alternately stacked to form a laminated structure containing 3 to 15 layers of copper electrodes. Each magnetic green sheet is located between two adjacent copper electrode layers, with the through-hole positions precisely aligned. The alignment accuracy between layers is controlled within ±10 μm by X-ray tomography. The stacking is carried out in an isostatic press at a pressure of 50 MPa to 100 MPa for 30 seconds to obtain an initial laminated green body. Subsequently, an isostatic pressing pretreatment is performed: the green body is held at a pressure of 200 MPa to 300 MPa for 5 minutes in 25°C silicone oil, which increases the overall density of the green body to more than 65% of the theoretical density, while controlling the shrinkage difference to within 0.7%.
[0033] Furthermore, the laminated green bodies are placed in a high-temperature sintering furnace with controlled atmosphere to undergo a multi-stage gradient sintering process. The furnace chamber is divided into six independent temperature zones, each 100 mm in length, with a temperature control accuracy of ±1℃ and an axial temperature gradient of <5℃. A zirconia oxygen partial pressure sensor is installed inside the furnace to monitor and control the oxygen partial pressure in real time within 10⁻¹. 5 The temperature range is from atm to 10⁻¹² atm. First stage degreasing: Under a nitrogen atmosphere, the temperature is increased from room temperature to 400℃ at a rate of 1℃ / min and held for 2 hours to completely decompose the organic carrier. The exhaust port is connected to a condenser-adsorption device to capture decomposition products such as α-terpinene, water, and CO2. Mass spectrometry monitoring confirms that there are no sulfur- or chlorine-containing residues.
[0034] The second stage, pre-sintering: The atmosphere is switched to 95% N2 + 5% H2, and the temperature is increased to 800℃ at 2℃ / min, held for 1 hour to remove residual hydrocarbons and activate the interfacial stability of the passivation layer. The third stage, co-firing densification: The atmosphere is switched to pure nitrogen, and the temperature is increased to 1180℃ to 1220℃ at 0.5℃ / min, held for 4 to 6 hours. During this stage, the magnetic material is densified, with a relative density >98% and an average grain size of 8μm to 20μm; the copper electrode, due to the barrier of the composite passivation layer, has a grain size limited to 5μm to 15μm, and no copper ferrite phase is formed. The fourth stage, isothermal diffusion annealing: An isostatic pressure of 0.1MPa to 0.5MPa is applied at 1180℃ in a nitrogen atmosphere for 30 to 90 minutes, inducing a trace diffusion of SiO2 components to the interface, forming a silicate transition layer with a thickness of 20nm to 50nm, and increasing the interfacial bonding strength to over 45MPa. Fifth stage cooling: The temperature is lowered to 600℃ at a rate of 1℃ / min, switching to high-purity argon gas, while a longitudinal magnetic field of 0.05T to 0.2T is applied, and the temperature is slowly cooled to room temperature at a rate of 0.3℃ / min to guide the formation of weak copper grains. <111> Texture reduces grain boundary resistance.
[0035] In a preferred embodiment of the present invention, after sintering, the blank is end-face ground and polished for 30 seconds under nitrogen protection using a diamond suspension with a particle size of 1 μm to remove surface oxides and expose a pure copper surface. Then, silver paste is coated on both ends. The silver paste consists of 0.5 μm spherical silver powder, Bi₂O₃-ZnO-B₂O₃ glass powder, and an organic carrier (ethyl cellulose / terpineol = 1:9) in a mass ratio of 85:5:10, with a coating thickness of 50 μm. Sintering is then performed at 600℃ for 30 minutes to form metallurgically bonded end electrodes with a contact resistance of <0.5 mΩ. The device is leak-tested by helium mass spectrometry, and the leakage rate is <1×10⁻⁻⁻⁶. 9 Pa·m³ / s, ensuring no through-hole defects.
[0036] Furthermore, an epoxy resin encapsulation layer is coated on the device surface. The encapsulation material is composed of bisphenol A type epoxy resin (E-51), methyl hexahydrophthalic anhydride (MHHPA), and nano-aluminum nitride (AlN, particle size 30-100nm, KH-550 modified) in a mass ratio of 60:30:10. After mixing, the mixture is degassed under vacuum and coated to a thickness of 20μm to 50μm. It is then cured at 120℃ for 2 hours. The thermal conductivity of the encapsulation layer, measured by laser scintillation, is 3.5W / m·K to 4.2W / m·K, and the coefficient of thermal expansion is 8.5±0.5ppm / ℃. It matches well with the magnetic core (9.8ppm / ℃) and copper electrode (17ppm / ℃), and there is no delamination at the interface.
[0037] As a preferred embodiment of the present invention, the magnetic core is subjected to magnetic field heat treatment after sintering: under a 1.5T DC magnetic field and an argon atmosphere, it is cooled from 600℃ to room temperature at a rate of 0.1℃ / min, so that the magnetic grains are preferentially oriented along the magnetic field direction, the permeability anisotropy ratio is increased to more than 1.5, the initial permeability at 1MHz is >800, and the eddy current loss is reduced by 22%.
[0038] The following specific examples and comparative figures, combined with quantitative data, verify the technical effectiveness of the present invention.
[0039] Example 1: An 0805 package (3.2mm × 2.5mm × 2.2mm) inductor with an inductance of 1.0μH was fabricated using the complete process of this invention. The copper powder has a particle size of 1.5μm. The composite passivation layer consists of Al₂O₃ 5nm / HfO₂ 8nm / SiO₂ 10nm, with 2at% phosphorus doping and 0.3at% fluorine doping. The magnetic material is doped with 0.3mol% Bi₂O₃ and 0.2mol% V₂O₅. The peak sintering temperature is 1200℃, held for 5 hours, followed by diffusion annealing at 0.3MPa for 60 minutes. A 0.1T magnetic field is applied during the cooling stage. The encapsulation layer contains 5wt% nano-AlN.
[0040] Comparative Example 1: It adopts a traditional silver electrode Ni-Zn ferrite multilayer inductor, silver paste printing, co-firing temperature of 950℃, no interface modification, no magnetic field cooling, and no nanofiller encapsulation.
[0041] Comparative Example 2: Unmodified copper powder was directly co-fired without a composite passivation layer, and the rest of the process was the same as in Example 1.
[0042] Comparative Example 3: Single-layer SiO2 passivation (15nm) was used, without Al2O3 / HfO2, and the rest was the same as in Example 1.
[0043] The test data is shown in the table below: The data in the table show that Example 1 is superior to the comparative example in all key indicators such as DC resistance, saturation current, Q value, thermal stability, and interface strength.
[0044] In Comparative Example 2, due to the lack of a passivation layer, copper reacted violently with ferrite, resulting in an open circuit at the electrode. Comparative Example 3 shows that monolayer SiO2 cannot effectively block ion diffusion, resulting in severe interface degradation and a significant decrease in performance.
[0045] Furthermore, the device in Example 1, tested according to the AEC-Q200 standard, exhibited an inductance temperature coefficient of +28ppm / ℃ within the range of -55℃ to 150℃, and showed no damage in a drop ball test (50g steel ball, 50cm height), meeting the reliability requirements of automotive electronics. The production line achieved a yield rate of 99.6%, a daily capacity of 120,000 units, and a cost reduction of 62% compared to Comparative Example 1.
[0046] Example 2 Based on the same inventive concept as the preparation method of the copper co-fired inductor in Embodiment 1 above, such as Figure 2 As shown, this invention also provides a copper co-fired inductor, which is prepared using the aforementioned method, including a multilayer magnetic core, copper electrodes embedded within the magnetic core, silver end electrodes at both ends of the device, and an epoxy resin encapsulation layer covering the surface of the device. The multilayer magnetic core is formed by dense sintering of multiple layers of modified Ni-Zn ferrite sheets, with a relative density greater than 98%, an average grain size of 8μm to 20μm, a saturation magnetic flux density Bs greater than 420mT, and an initial permeability μi greater than 800 at 1MHz. The copper electrodes are formed by sintering copper particles coated with a three-layer composite passivation-diffusion barrier layer of Al2O3 / HfO2 / SiO2, with a volume resistivity of less than 2.5μΩ·cm and a porosity of less than 1.5%. There is no copper-iron interface between the copper electrode and the magnetic substrate. The device features an oxygen phase, no amorphous layer, and no microcracks, with an interfacial bonding strength greater than 45 MPa. The contact resistance between the silver and copper electrodes is less than 0.5 mΩ. The thermal expansion coefficient of the epoxy resin encapsulation layer matches the magnetic core and copper electrodes within ±5 ppm / ℃. The copper electrodes form a three-dimensional comb-like interlocking structure inside the magnetic core, achieving interlayer electrical connection through a through-hole structure with a diameter of 0.1 mm to 0.3 mm and a distribution density of 4 to 16 holes per square centimeter, resulting in an interlayer resistance of less than 1 mΩ. At 25℃ and 100 kHz, the device exhibits a DC resistance of less than 0.5 mΩ, a saturation current greater than 30 A, and a Q value greater than 80. At 125℃ and 1 MHz, the Q value decay rate is less than 15%, and the DC resistance temperature rise coefficient is less than 0.3% / ℃. After 1000 thermal cycle tests from -40℃ to 150℃, the inductance change rate is less than ±2%.
[0047] Through the foregoing detailed description of the preparation method of the copper co-fired inductor, those skilled in the art can clearly understand the copper co-fired inductor in this embodiment. Therefore, for the sake of brevity, it will not be described in detail here.
[0048] The foregoing has shown and described the basic principles, main features, and advantages of the present invention. It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above, and that the invention can be implemented in other specific forms without departing from its spirit or essential characteristics. Therefore, the embodiments should be considered illustrative and non-limiting in all respects, and the scope of the invention is defined by the appended claims rather than the foregoing description. Thus, all variations falling within the meaning and scope of equivalents of the claims are intended to be included within the scope of the invention. No reference numerals in the claims should be construed as limiting the scope of the claims.
[0049] Furthermore, it should be understood that although this specification describes embodiments, not every embodiment contains only one independent technical solution. This narrative style is merely for clarity. Those skilled in the art should consider the specification as a whole, and the technical solutions in each embodiment can also be appropriately combined to form other embodiments that can be understood by those skilled in the art.
Claims
1. A method for preparing a copper co-fired inductor, characterized in that, include: Spherical electrolytic copper powder with an average particle size of 0.8 μm to 2.5 μm was surface pretreated, and the pretreated copper powder was placed in a fluidized bed reactor for atomic layer deposition under a nitrogen atmosphere. Trimethylaluminum vapor and deionized water vapor are introduced, and deposition is carried out at 120°C for 15 to 40 cycles to form an initial passivation layer of aluminum oxide with a thickness of 3 nm to 8 nm. By switching the precursor to tetrahafnium and ozone, a hafnium oxide intermediate layer with a thickness of 5 nm to 12 nm is formed by deposition at 150 °C for 20 to 50 cycles. Then, by switching the precursor to trisilane and oxygen, a silicon dioxide outer layer with a thickness of 8 nm to 15 nm is formed by deposition at 180 °C for 25 to 60 cycles. This yields modified copper powder with a three-layer composite passivation-diffusion barrier layer of Al2O3 / HfO2 / SiO2 on the surface. The modified copper powder was mixed with an organic carrier at a mass ratio of 75:25 and then milled by three rollers for 4 hours to obtain a copper electrode slurry with a viscosity of 8000 cP to 12000 cP and a solid content of 75 wt%. The copper electrode paste is screen-printed onto a green ceramic tape with a thickness of 50μm to 150μm to form a comb-shaped electrode structure with a width of 0.1mm to 0.5mm and a spacing of 0.05mm to 0.2mm. After printing, it is dried at 80°C for 10 minutes to form a copper electrode green layer. Modified Ni-Zn ferrite green sheets are provided, which are mixed with polyvinyl butyral at a mass ratio of 95:5 and then pressed into magnetic green sheets with a thickness of 100μm to 300μm. The copper electrode green sheet and the magnetic green sheet are alternately stacked to form a stacked structure of 3 to 15 copper electrodes. Each magnetic green sheet is located between two adjacent copper electrode layers. The stacking pressure is 50 MPa to 100 MPa, and the pressure is held for 30 seconds to obtain a stacked green body. The stacked green body is placed in an atmosphere-controlled sintering furnace and multi-stage gradient sintering is performed, namely the first stage of debinding, the second stage of pre-sintering, the third stage of co-firing densification, and the fourth stage of cooling. After sintering, the end face of the inductor blank is ground and cleaned, silver paste is applied to form silver terminal electrodes, and an epoxy resin encapsulation layer is applied to the surface of the device.
2. The preparation method according to claim 1, characterized in that, After the co-firing densification stage is completed and before the cooling stage begins, an isothermal diffusion annealing step is added: under a nitrogen atmosphere at 1180°C, an isostatic pressure of 0.1 MPa to 0.5 MPa is applied for 30 to 90 minutes to promote the diffusion of SiO2 components to the interface to form a silicate transition layer with a thickness of 20 nm to 50 nm, thereby enhancing the interfacial bonding strength between the copper electrode and the magnetic substrate to greater than 45 MPa.
3. The preparation method according to claim 1, characterized in that, The copper electrode slurry contains nano-magnesium oxide particles with a particle size of 50nm to 200nm, and the amount added is 0.5% to 2.0% of the copper powder mass.
4. The preparation method according to claim 1, characterized in that, The laminated green body undergoes isostatic pressing pretreatment before co-firing: it is held at 200MPa to 300MPa for 5 minutes with 25℃ silicone oil as the medium, which increases the density of the green body to more than 65% of the theoretical density, and the difference in linear shrinkage between the copper electrode and the magnetic matrix is less than 0.7%.
5. The preparation method according to claim 1, characterized in that, The sintering furnace employs a zoned temperature control structure during the co-firing densification stage. The furnace chamber has six independent temperature zones, each 100mm in length, with a temperature control accuracy of ±1℃ and an axial temperature gradient of less than 5℃. An oxygen partial pressure sensor is also included to control the oxygen content of the atmosphere to be within 10⁻¹. 5 The range is from 10⁻¹² atm to 10⁻¹² atm.
6. The preparation method according to claim 1, characterized in that, The outer silicon dioxide layer is doped with 1% to 5% phosphorus during deposition, and triphosphine is introduced as a co-precursor to form a phosphosilicate glass structure; the alumina layer is doped with 0.1 at% to 0.5 at% fluorine during deposition, and boron trifluoride diethyl ether complex is introduced to reduce the dielectric constant to 7.
5.
7. The preparation method according to claim 1, characterized in that, Before printing, the comb-shaped electrode structure is first laser-drilled on the green ceramic tape to form a through-hole structure with a hole diameter of 0.1 mm to 0.3 mm and a tolerance of ±5 μm. After the inner wall of the hole is treated with argon plasma, 100 nm nano silver sol is sprayed to form a conductive seed layer, and then copper paste is printed to fill it.
8. The preparation method according to claim 1, characterized in that, During the cooling stage, after switching to an argon atmosphere at 600°C, a longitudinal magnetic field of 0.05T to 0.2T is simultaneously applied to guide copper grains to form along the direction of the magnetic field. <111> Texture; the magnetic green sheet is subjected to argon plasma activation treatment for 30 seconds before stacking, with a power density of 5W / cm².
9. The preparation method according to claim 1, characterized in that, The epoxy resin encapsulation layer is doped with 5% by mass of nano-aluminum nitride particles with a particle size of 30nm to 100nm; the magnetic core is subjected to magnetic field heat treatment after sintering to make the magnetic core grains preferentially oriented along the magnetic field direction.
10. A copper co-fired inductor, prepared by any one of claims 1 to 9, characterized in that, It includes a multilayer magnetic core, copper electrodes embedded inside the magnetic core, silver end electrodes at both ends of the device, and an epoxy resin encapsulation layer covering the surface of the device. The multilayer magnetic core is formed by dense sintering of multiple modified Ni-Zn ferrite sheets; the copper electrode is formed by sintering copper particles coated with a three-layer composite passivation-diffusion barrier layer of Al2O3 / HfO2 / SiO2; the contact resistance between the silver end electrode and the copper electrode is less than 0.5mΩ; the thermal expansion coefficient of the epoxy resin encapsulation layer matches the multilayer magnetic core and the copper electrode within ±5ppm / ℃.